The effect of intention to act and knowledge of environmental issues on environmental behavior - Fauzul Iman; Mieke Miarsyah; Diana Vivanti Sigit (University of Muhammadiyah Malang, 2019)
Intention to act and environmental issues knowledge has been assumed as the two variables which affect people’s environmental behavior. This study aimed at determining the correlations between variables (i.e. intention to act, environmental issues knowledge, and environmental behavior) on biology teachers in State High Schools of Pandeglang Regency. This survey research used quantitative approach. The sample was 51 teachers chosen using simple random sampling. Meanwhile, the population was 61 teachers in State High Schools of Pandeglang Regency. The data gained were analyzed using path analysis. The results showed that environmental knowledge gives direct impact on environmental behavior with coefficient value was 0.472. The same phenomena were also occurred in the intention to act towards the teachers’ environmental behavior (0.508). In addition, the intention to act was directly influenced by environmental knowledge (0.364), while the environmental behavior was indirectly affected by environmental knowledge (0.185). Thus, the findings of this study can be basic information to determine the most proper strategy to cultivate a good environmental behavior.